Systemic sclerosis sine scleroderma: clinical and serological features and relationship with other cutaneous subsets in a large series of patients from the national registry 'SPRING' of the Italian Society for Rheumatology. Issue 1 (3rd March 2023) - De Angelis, Rossella; Ferri, Clodoveo; Giuggioli, Dilia; Bajocchi, Gianluigi; Dagna, Lorenzo; Bellando-Randone, Silvia; Zanframundo, Giovanni; Foti, Rosario; Cacciapaglia, Fabio; Cuomo, Giovanna; Ariani, Alarico; Rosato, Edoardo; et al.
Abstract : Objective: To describe demographic, clinical and laboratory features of systemic sclerosis sine scleroderma (ssSSc) in a large multicentre systemic sclerosis (SSc) cohort. Methods: Data involving 1808 SSc patients from Italian Systemic sclerosis PRogression INvestiGation registry were collected. The ssSSc was defined by the absence of any cutaneous sclerosis and/or puffy fingers. Clinical and serological features of ssSSc were compared with limited cutaneous (lcSSc) and diffuse cutaneous (dcSSc) subsets. Results: Among patients with SSc, only 61 (3.4%) were classified as having ssSSc (F/M=19/1). Time from Raynaud's phenomenon (RP) onset to diagnosis was longer in ssSSc (3 years, IQR 1–16.5) than lcSSc (2 years, IQR 0–7), and dcSSc (1 year, IQR 0–3) (p<0.001). Clinical ssSSc phenotype was comparable to lcSSc, except for digital pitting scars (DPS) (19.7% vs 42%, p=0.01), but significantly milder than dcSSc, particularly for digital ulcers (DU) (6.6% vs 35.7%, p<0.001), oesophagus (46.2% vs 63.5%, p=0.009), lung (mean diffusion capacity for carbon monoxide 72.2±19.6 vs 62.4±22.8, p=0.009; mean forced vital capacity 105.6±21.7 vs 89.2±20.9, p<0.001) and major videocapillaroscopic alterations (late pattern 8.6% vs 47.6%, p<0.001). Moreover, in ssSSc the percentages of anticentromere and antitopoisomerase were comparable to lcSSc (40% and 18.3% vs 36.7% and 26.6%), but divergent respect to dcSSc (8.6% and 67.4%, p<0.001). Conclusion: The ssSSc is a quite rare disease variant characterised by clinico-serological features comparable to lcSSc, but significantly different from dcSSc. Overall, longer RP duration, low percentages of DPS and peripheral microvascular abnormalities, and increased anti-centromere seropositivity distinguish ssSSc. Further investigations based on national registries might provide useful insights on the actual relevance of the ssSSc within the scleroderma spectrum.